2019
DOI: 10.2174/2542579x01666190212150457
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Fluoride Nanoparticles for Preventing Dental Caries

Abstract: Background: Dental caries is still a major public health problem. The use of fluoride is one of the most effective ways to prevent tooth decay. Objective: The purpose of this research was to investigate the effectiveness of fluoride entrapped in chitosan nanoparticles in vivo. Methods: Sodium fluoride was loaded in chitosan via ionic gelation of tripolyphosphate nanoparticles. Characterization of nanoparticles was investigated by using the zeta potential, size of particles, loading capacities, encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, chitosan as a carrier was the most effective polymer, ensuring continuous delivery of the caries protective agent. The results of an experimental study by Ebrahim et al also supported the promising action of fluoride/chitosan nanoparticles [ 55 ]. Up to 2017, there was only one clinical study that reported the effect of the use of fluoride ions incorporated into bioadhesive fluoride tablets [ 125 ].…”
Section: Applications Of Polysaccharide Micro- and Nanoparticles In Pediatric Dentistrymentioning
confidence: 88%
“…However, chitosan as a carrier was the most effective polymer, ensuring continuous delivery of the caries protective agent. The results of an experimental study by Ebrahim et al also supported the promising action of fluoride/chitosan nanoparticles [ 55 ]. Up to 2017, there was only one clinical study that reported the effect of the use of fluoride ions incorporated into bioadhesive fluoride tablets [ 125 ].…”
Section: Applications Of Polysaccharide Micro- and Nanoparticles In Pediatric Dentistrymentioning
confidence: 88%
“…There have been many studies that documented the combination of chitosan with various other ingredients normally used in dentifrices, such as NaF, SnCl 2, KNO 3 , HA, and SnF 2, with increased effectiveness of the dentifrice in some of the studies [ 41 , 42 ]. In their report on the commercially available, fluoride-free chitosan-based dentifrice, tissue loss was significantly reduced, according to Ganss et al Using NaF- and Sn-based dentifrices has also been linked to similar results in terms of halting the deterioration of the dentin matrix and enamel [ 43 , 44 , 45 ]. These results are explained by the strong affinity of chitosan for binding to zeta potential-negative structures like enamel and salivary pellicles, as well as the cationic character of chitosan in combination with a low pH.…”
Section: Applications In Dentistrymentioning
confidence: 99%
“…Ebrahimi and colleagues stated that the synthesized fluoride/chitosan nanoparticles were a promising way to provide fluoride for the early prevention of tooth decay. 19 Simeonov and colleagues in their research developed a chitosan microgel hybrid which showed an effective agent for enhancing remineralization of early caries development and carried out an early-stage approach that has been tested and proved effective for early demineralization of enamel remineralization. 20 In elementary school children, the level of oral hygiene is low, so it can increase the incidence of dental and oral diseases caused by various microorganisms.…”
Section: Chitosan As Dental Protectionmentioning
confidence: 99%